Reading the Reformations
1 online resource
Keywords: In the last thirty years, understandings of the European reformations have been transformed. A generation of scholars has demonstrated how radically wide-ranging these movements were. Across family life, politics, material culture and philosophy, the reformations are now at the very heart of our understanding not just of early modern Europe, but of religion and identity in general. This volume collects recent work from past and present members of the European Reformation Research Group, exploring key fronts in contemporary Reformation Studies, achieving a broad view of how historiography has developed in recent decades – and where it seems set to go next.